IMPLEMENTASI PERATURAN MENTERI KEUANGAN (PMK) NOMOR 91/PMK.03/2015 TENTANG PENGURANGAN ATAU PENGHAPUSAN SANKSI ADMINISTRASI DI KPP PRATAMA PEKANBARU SENAPELAN - Syafitri, Atika; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tax are the primary source of state funds and development, thus tax is potential enough to determine the development success. The goverment efforts to improve tax revenue from tax sector keeps increased, one of them is improve the legislative regulations,thus tax’s regulation will be received by the society. The aim of this study is to describe the implementation of Minister of Finance Regulation No. 91/PMK.03/2015 inKPP Pratama Pekanbaru Sanepelan about removal or reduction of administration sanction and to identify the factors that affect its implementation.Concept of the theory used is policy implementation model of Van Meter Van Horn says there are 6 (six) indicators to measure the success of public policy implementation, namely: standards and policy objectives, policy resources, communication activity between organizations and activities executor, the executor characteristics, socio-economic and political conditions, dispositions and attitudes implementors. This study used a qualitative descriptive study. In collecting the data, the authors use the technique of observation and interview. By using key informants as a source of information and data analysis.The result of this study shown that the implementation Minister of Finance Regulation No. 91/PMK.03/2015 inKPP Pratama Pekanbaru Sanepelan is maximal especially in policy resources indicator, whereas in the other indicators are quite good. This study also identify two factors that affect the policy’s implementasion are the awareness of the implementer (tax workers and tax payers) and economic conditions. According to this study, KPP Pratama Pekanbaru Senapelanshould control the tax payers directly and manage them. It also needs to improve the awareness of tax payers toward the fasilities that provided, thus it would increase the willness of the tax payers to pay the tax in Pekanbaru.Key Words: Implementation, Regulation, Reduction of Penalty